2005
DOI: 10.1161/01.hyp.0000169972.96201.8e
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy Is More Prevalent in Blacks Than Whites in the General Population

Abstract: Abstract-Although recent studies have suggested that blacks compared with whites have an increased prevalence of left ventricular hypertrophy, it remains uncertain whether this is true despite adjustment for body composition (fat mass and fat-free mass) and when assessed by cardiac MRI in the general population. The Dallas Heart Study is a population-based study of Dallas County in which 1335 black and 858 white participants 30 to 67 years of age underwent detailed assessment including dual-energy x-ray absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
242
5
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 306 publications
(263 citation statements)
references
References 32 publications
3
242
5
2
Order By: Relevance
“…In health, LVM is largely determined by the metabolic requirements of LBM, 5,6 which differs between ethnic groups. Compared with Caucasians, LBM is higher in American Blacks 46 and lower in Asian Indians. 8 Therefore in disease, LVH may be underdiagnosed in Asian Indians, where measured LVM may appear normal; however, their small build and low LBM is compatible with a lower LVM and as such will remain undetected.…”
Section: Discussionmentioning
confidence: 69%
“…In health, LVM is largely determined by the metabolic requirements of LBM, 5,6 which differs between ethnic groups. Compared with Caucasians, LBM is higher in American Blacks 46 and lower in Asian Indians. 8 Therefore in disease, LVH may be underdiagnosed in Asian Indians, where measured LVM may appear normal; however, their small build and low LBM is compatible with a lower LVM and as such will remain undetected.…”
Section: Discussionmentioning
confidence: 69%
“…40,41 Apart from increased left ventricular mass in Africans, Li et al 44 indicated recently that African Americans have higher BP variability than European Americans, contradicting a small study performed in England (N¼26) that indicated no ethnic differences. 45 Li et al 44 argue that the higher BP variability values of Africans are consistent with the prognostic value of BP variability, and the higher incidence and mortality of cardiovascular disease in Africans.…”
Section: Discussionmentioning
confidence: 98%
“…African populations are known to have increased left ventricular mass and a two-to three-fold higher prevalence of left ventricular hypertrophy in the general population, 40 with increased left ventricular mass already originating from late childhood. 41 Furthermore, Havranek et al 42 indicated that ECG left ventricular hypertrophy contributes more to the risk of cardiovascular mortality in African Americans than in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Details of cardiac magnetic resonance imaging have been previously described for baseline imaging24, 25 and more recently described for follow‐up imaging 26. In brief, cardiac magnetic resonance imaging was performed using 1 of 2 comparable 1.5‐Tesla systems (Philips Medical System, Best, The Netherlands) at baseline and a 3‐Tesla system (Achieva, Philips Medical Systems, Best, The Netherlands) at follow‐up.…”
Section: Methodsmentioning
confidence: 99%